Genetic and Pharmacologic Targeting of Glycogen Synthase Kinase 3β Reinforces the Nrf2 Antioxidant Defense against Podocytopathy - Zhou, Sijie (J Am Soc Nephrol, 2016)
Evidence suggests that the glycogen synthase kinase 3 (GSK3)–dictated nuclear exclusion and degradation of Nrf2 is pivotal in switching off the self-protective antioxidant stress response after injury. Here, we examined the mechanisms underlying this regulation in glomerular disease. In primary podocytes, doxorubicin elicited cell death and actin cytoskeleton disorganization, concomitant with overactivation of GSK3β (the predominant GSK3 isoform expressed in glomerular podocytes) and minimal Nrf2 activation. SB216763, a highly selective small molecule inhibitor of GSK3, exerted a protective effect that depended on the potentiated Nrf2 antioxidant response, marked by increased Nrf2 expression and nuclear accumulation and augmented production of the Nrf2 target heme oxygenase-1. Ectopic expression of the kinase-dead mutant of GSK3β in cultured podocytes reinforced the doxorubicin-induced Nrf2 activation and prevented podocyte injury. Conversely, a constitutively active GSK3β mutant blunted the doxorubicin-induced Nrf2 response and exacerbated podocyte injury, which could be abolished by treatment with SB216763. In murine models of doxorubicin nephropathy or nephrotoxic serum nephritis, genetic targeting of GSK3β by doxycycline-inducible podocyte-specific knockout or pharmacologic targeting by SB216763 significantly attenuated albuminuria and ameliorated histologic signs of podocyte injury, including podocytopenia, loss of podocyte markers, podocyte de novo expression of desmin, and ultrastructural lesions of podocytopathy (such as foot process effacement). This beneficial outcome was likely attributable to an enhanced Nrf2 antioxidant response in glomerular podocytes because the selective Nrf2 antagonist trigonelline abolished the proteinuria-reducing and podocyte-protective effect. Collectively, our results suggest the GSK3β-regulated Nrf2 antioxidant response as a novel therapeutic target for protecting podocytes and treating proteinuric glomerulopathies.